A general multi-scale modeling framework for two-phase simulation of multi-stream plate-fin heat exchangers. (August 2020) - Niroomand, R.; Saidi, M.H.; Hannani, S.K.
Highlights: A comprehensive model, including most important features of MSPFHEs is stablished. Layer by layer simulation of two-phase cross-flow MSPFHEs is carried out. 3D temperature distribution in the solid matrix of MSPFHEs is presented. Solid matrix temperature is calculated considering conduction in all directions. Abstract: Compact heat exchangers are among the vital components used in various industries. In this study, a general framework has been developed with a multi-scale point of view for three-dimensional simulation of multi-stream plate-fin heat exchangers. The most important features in the MSPFHEs simulation, such as phase change phenomena, multi-component mixtures, multiple streams, transversal, lateral and longitudinal conduction, non-uniformity of inlet flow, variable fluid properties, and heat leakage are simultaneously considered in this model. The modular form of the model structure has facilitated layer-by-layer simulation of cross flow heat exchangers as well as parallel flow ones. Our model has been successfully validated with numerical and experimental case studies. Periodic boundary conditions are developed for simulating heat exchangers with a high number of layers to reduce the computational cost. The results for a challenging six-stream test case show that when the number of layers for each stream is more than 15, results converge to the periodic boundary condition case. The total simulation time is decreased by 98.1% for a heat exchanger with 40 repeating unit cells. Liquefied natural gas production has been decreased by 5.8% due to the non-uniformity of natural gas at the entrance of the six-stream test case. Fluid temperature, and vapor quality distributions for a multi-component two-phase cross-flow MSPFHE have been presented. A dead zone is observed in the results of the cross-flow heat exchanger that does not have a significant contribution to the heat exchange. Results show that the total heat exchange between streams has been decreased by 8.5% in comparison to the parallel-flow ones.